A human iPSC line capable of differentiating into functional macrophages expressing ZsGreen: a tool for the study and in vivo tracking of therapeutic cells. (21st May 2018) - Lopez-Yrigoyen, Martha; Fidanza, Antonella; Cassetta, Luca; Axton, Richard A.; Taylor, A. Helen; Meseguer-Ripolles, Jose; Tsakiridis, Anestis; Wilson, Valerie; Hay, David C.; Pollard, Jeffrey W.; Forrester, Lesley M.
Abstract : We describe the production of a human induced pluripotent stem cell (iPSC) line, SFCi55-ZsGr, that has been engineered to express the fluorescent reporter gene, ZsGreen, in a constitutive manner. The CAG-driven ZsGreen expression cassette was inserted into the AAVS1 locus and a high level of expression was observed in undifferentiated iPSCs and in cell lineages derived from all three germ layers including haematopoietic cells, hepatocytes and neurons. We demonstrate efficient production of terminally differentiated macrophages from the SFCi55-ZsGreen iPSC line and show that they are indistinguishable from those generated from their parental SFCi55 iPSC line in terms of gene expression, cell surface marker expression and phagocytic activity. The high level of ZsGreen expression had no effect on the ability of macrophages to be activated to an M(LPS + IFNγ), M(IL10) or M(IL4) phenotype nor on their plasticity, assessed by their ability to switch from one phenotype to another. Thus, targeting of the AAVS1 locus in iPSCs allows for the production of fully functional, fluorescently tagged human macrophages that can be used for in vivo tracking in disease models. The strategy also provides a platform for the introduction of factors that are predicted to modulate and/or stabilize macrophage function. This article is part of the theme issue 'Designer human tissue: coming to a lab near you'.